Peculiarities of neutron fields formation in the systems “neutron producing target – moderator” irradiated by high energy particles - Chigrinov, S.E.; Serafimovich, I.G.; Bournos, V.V.; Fokov, Yu.G.; Korneev, S.V.; Routkovskaia, C.C.; Mazanik, S.E.; Adamovich, A.A.; Kiyavitskaya, H.I.; Koulikovskaya, A.V.; Khilmanovich, A.M.; Martsynkevich, B.A.; et al. (Вопросы атомной науки и техники, 2005)
The theoretical and experimental evidence of similarity of neutron spectra formed in sub-critical systems driven by external proton and neutron beams